Influence of gaps in flange joints on the stress-strain state of the unit - A. R. Tusnin; V. D. Platonova (Vestnik MGSU)
Introduction. For the solution of engineering problems, the question of the actual operation of the building frame as a whole, taking into account the peculiarities of the operation of the joints connecting the load-bearing elements, is of interest. It is proposed to investigate the influence of initial gaps in flange “beam – column” type connections on strength and deformation characteristics of the joint solution. Special attention is paid to the operation of high-strength bolts with pretensioning in the “tension-bending” mode of operation. In this article, the configuration of the experimental model is proposed, the method of fixing the value of stresses in bolts at three points is chosen, which makes it possible to take into account stresses not only along the axis, but also in the plane of the cross-section of the bolt.Materials and methods. A literature review of the subject of the influence of initial imperfections in flange joints is carried out, the question of disadvantages of existing approaches to the analytical calculation of assemblies on the basis of Russian and foreign normative documents is considered. Experimental installation and prototypes are described, recommendations for experimental studies of a frame fragment with two types of joints are given. The installation and prototypes are developed on the basis of the results of numerical calculation of finite element models.Results. A test of a stud with the declared strength class 8.8 to determine its actual mechanical characteristics, a tensile test of a stud with slots to assess the reliability of strain gauge data and adjust the design of experimental specimens taking into account the test results, testing of joint solutions of two types of configurations, processing and analyzing the test results were carried out.Conclusions. The methodology of experiment execution on the research subject is substantiated, the character of the influence of the formed gap on the stresses in the elements of the joint is determined.